Spatial Representation of Hippocampal Place Cells in a T-Maze with an Aversive Stimulation - Okada, Sakura; Igata, Hideyoshi; Sasaki, Takuya; Ikegaya, Yuji (Frontiers in Neural Circuits, 2017)
The hippocampus contains place cells representing spaces in an environment, and these place cells have been suggested to play a fundamental role in the formation of a cognitive map for spatial processing. However, how alterations in the firing patterns of place cells in response to aversive events encode the locations tied to these aversive events is unknown. Here, we analyzed spiking patterns of place cell ensembles in the dorsal hippocampal CA1 region of rats performing a T-maze alternation task with an aversive air-puff stimulation applied at a specific location on one side of a trajectory. The intensity of the air puff was adjusted so that the rats decreased their running speed before passing the aversive location. The addition of the aversive stimulus induced reorganization of place cell ensembles on both left and right trajectories with and without the aversive stimulus, respectively. Specifically, the animals showed a more abundant spatial representation in the vicinity of the aversive location. Removing the aversive stimulus induced new spatial firing patterns on both of the trajectories that differed from those both before and during application of the aversive stimulus. These results demonstrate that hippocampal spatial maps are flexibly reorganized to represent particular aversive events.